Pengaruh Perceived Price, Public Relation, Dan Wom Terhadap Keputusan Penggunaan Jasa Fitness Center (Studi Pada Member Max Gym Fitness Center Probolinggo) - Ainul Yaqin; Dedi Joko Hermawan; Agung Yatiningrum (Universitas Panca Marga, 2024)
This research was conducted on MAX GYM Fitness Center Probolinggo Members with the aim of this research being to examine Perceived Price, Public Relations, and WOM on Decisions to Use Fitness Center Services among MAX GYM Fitness Center Probolinggo Members. The population in this study were members of the MAX GYM Fitness Center Probolinggo. The sample in this study used the technique used in this research, namely the slovin technique, totaling 60 members of the MAX GYM Fitness Center Probolinggo. Analysis was carried out using the Multiple Linear Regression model. The results of this research show that: (1). Perceived Price has a positive and significant influence on the Perceived Price variable on Service Use Decisions, (2). The Public Relations variable has a positive and significant effect on the Public Relations variable on Service Use Decisions, (3). WOM has a positive and significant influence on the WOM variable on service use decisions.